Agreement on the International Carriage of Perishable Foodstuffs and on the Special Equipment to be Used for Such Carriage: ATP as amended on 30 September 2015 - United Nations Economic Commission for Europe (United Nations, 2015)
The ATP is an Agreement between States, and there is no overall enforcing authority. In practice, highway checks are carried out by Contracting Parties, and non-compliance may then result in legal action by national authorities against offenders in accordance with their domestic legislation.